Mitochondrial fusion protein 2 affects intracellular survival of brucella abortus a19 by regulating endoplasmic reticulum stress and apoptosis - Zhenyu XU; Qin YANG; Xiaoyu DENG; Yimei XU; Zhongchen MA; Chuangfu CHEN (Kafkas Universitesi Veteriner Fakültesi Dergisi, 2024)
Mitochondrial fusion protein 2 (MFN2) deficiency has been shown to hinder the survival of bacteria in macrophages. Endoplasmic reticulum stress and apoptosis are vital defense mechanisms against Brucella infection, but the specific role of MFN2 in Brucella-infected macrophages remains unclear. In this study, we aimed to investigate the role of MFN2 in the infection of macrophages by Brucella abortus strain A19. The levels of CHOP and GRP78, which are molecules associated with endoplasmic reticulum stress, as well as Caspase-3 and BAX, which are pro-apoptotic molecules, were measured using confocal microscopy, qRT-PCR and Western blot in cell models infected with B. abortus A19. Additionally, the apoptosis rate of these cell models was assessed using flow cytometry. Our findings revealed a significant decrease in MFN2 levels 24 h post B. abortus A19 infection of macrophages. Interfering with MFN2 in macrophages led to an increase in Brucella-induced up-regulation of CHOP, GRP78, Caspase-3, and BAX, consequently hindering the survival of B. abortus A19 in macrophages. Conversely, infecting macrophages that overexpress MFN2 with B. abortus A19 resulted in the down-regulation of CHOP, GRP78, Caspase-3, and BAX. MFN2 mediated the downregulation of endoplasmic reticulum stress and programmed cell death in B. abortus A19-infected macrophages, thereby supported the intracellular survival of Brucella. This is the first report to highlight the key role of MFN2 in the intracellular survival of Brucella, providing a new perspective for understanding the mechanisms involved and offering a potential research direction for the development of targeted therapeutic agents against brucellosis.